ANALISIS MAKNA KANYOUKU MENGGUNAKAN KATA 手 (TE) DALAM BAHASA JEPANG - Reza Handayani; Hermandra Hermandra; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack:In Japanese, idioms are called “kanyouku”, are build from a lot of word such as sense, body part, numeral, colour, nature thing, animal and plant. The purpouse of this research is to determine the lexical meaning and idiomatical meaning of the kanyouku which contains the word te and find out the structure of the formation of kanyouku te. Researchers obtained the data from the modern Japanese-Indonesian kanji dictionary, the Japanese-Japanese dictionary Kenji Matsuura, and the online dictionary Goo Jisho, Kotowza Kanyouku Hakkajiten, etc. The method used in this research is descriptive method. In collecting data library research is used, that is, using written sources to obtain data. The technique used in the collection of research data is the listening method. The theory used in this study is the theory of Muneo Inoue and Momiyama. The anaysis of data in this research are there are 18 kanyouku that use the word te. Based on data analysis that has been done shows that the word 手 te in forming idioms can produce a type of meaning consisting of 5 data which stated karada, seikaku, taido wo arawasu kanyouku (personality) 8 data which started Koui, dousa,koudou wo arawasu kanyouku (action) , and 5 data which stated Jouta, teidou,kachiw o arawasu kanyouku (condition and value). Key Words: Analysis, Meaning, Kanyouku, Te